The Effect of Digital Comics as a Learning Medium on Third-Grade Students’ Reading Study at SDN 1 Pejambon - Kartikadewi, Nurfaiza; Labudasari, Erna; Iman, Bagus Nurul (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the impact of using digital comics as a learning medium on the reading skills of third-grade students at SDN 1 Pejambon. This study was motivated by the limited variety of learning media used and the disparities in reading skills observed among students in the classroom, particularly in terms of reading fluency, pronunciation clarity, and comprehension of the text. The approach used was a quantitative method with a one-group pretest-posttest pre-experimental design, involving 20 third-grade students as research subjects. Data collection was conducted using reading test instruments and observation sheets covering indicators of letter and word recognition, reading fluency, clarity of pronunciation, and reading comprehension. Data analysis was performed using both descriptive and inferential methods with the aid of IBM SPSS software, version 27. The results revealed an increase in students’ average scores, from 73.50 in the pretest phase to 89.50 in the posttest phase. The results of the paired t-test confirmed that the difference between the scores before and after the intervention was significant, with t (19) = -12.426, p < 0.001, and an average increase of 16 points. These findings indicate that the use of digital comics is effective in improving students’ reading skills while making the reading learning process in elementary school more engaging.